INDUCTION OF LABOR BY PROSTAGLANDIN: A REVIEW FOR INDICATIONS AND RISK FOR CESAREAN SECTION - Tripathy, Pravati; Baby, Prasanna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Labor induction by medication is now preferred by many obstetricians. The impact of induction remains ambiguous, although many studies and systematic reviews have been conducted. Few studies have reported for its better outcomes while other studies with poor outcomes. The objective of the study is to identify the common indications of induction and the risk of cesarean section after induction. Methods: Various standardized databases, such as Pub Med, Scopus, and Google Scholar, were used to collect the scientific studies, where prostaglandin was used as drug of choice for induction of labor. The key words used were induction of labor, indications of induction, induction by misoprostol, induction and risk of cesarean section, etc. The survey spans over 22 years of study articles published from the year 1995-2017. Result: A total of 112 studies have been included to analyze the indications and risk of cesarean section. The most common indication found in most of the studies was post-term pregnancy. The risk of cesarean section varied from 3% to 48.7%. The common reasons for which the cesarean section was planned were, failed induction, nonprogress of labor, fetal distress, and undiagnosed CPD. Conclusion: Most of the studies recommend induction of labor as a safer option with lower risk of c-section.